The Students' Thinking Level in Solving Mathematics Problems Based on SOLO Taxonomy as Viewed from the Mathematics Anxiety - Ratri Candra Hastari; Dewi Anggreini; Kiki Wiyanti (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2021)
The SOLO (Structure of Observed Learning Outcome) taxonomy is an educational taxonomy suitable for organizing various types of learning. The SOLO taxonomy categorizes students' thinking into five levels: pre-structural, uni-structural, multi-structural, relational, and extended abstract. The purpose of this study was to describe the level of students' thinking in solving mathematics problems based on the SOLO taxonomy with high, medium, and low levels of mathematics anxiety. This type of research is descriptive qualitative research. This research was conducted in one of the junior high schools in Tulungagung City, East Java, Indonesia. The instruments used were a mathematics anxiety questionnaire, test based on the SOLO taxonomy, and interview guidelines. The data analysis used the Miles and Huberman model, which consists of three stages, namely data reduction, data presentation, and conclusion drawing or verification. The results showed that subjects with high mathematics anxiety had a uni-structural level of thinking. Second, subjects with moderate mathematics anxiety had a multi-structural level of thinking. Third, subjects with low mathematics anxiety have an extended abstract thinking level.